Variasi Fenotipe dan Profil Morfometri Sapi Madura Betina pada Berbagai Grade di Wilayah Sumber Bibit Kabupaten Pamekasan - Musdalifah, Faigah; Mudawamah; Humaidah, Nurul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to analyze the phenotypic variation and morphometric profiles of female Madura cattle across different grades in the breeding source area of Pamekasan Regency. A case study method was employed using a purposive sampling technique, involving 120 female Madura cattle aged 30–36 months, healthy, and non-pregnant. Data on qualitative phenotypic traits and morphometric profiles (shoulder height, body length, and chest girth) were analyzed using Chi-square and Q–Q Plot tests. The results showed that the phenotypic variation of female Madura cattle across grades did not differ significantly from the Indonesian National Standard (SNI) for Madura cattle (P > 0.05). The percentages of phenotypic conformity to the SNI in grades 1, 2, and 3 were 96.67%, 95.24%, and 93.75%, respectively, while non-conformities were 3.33%, 4.76%, and 6.75%. Morphometric profiles were also consistent with the SNI without significant differences (P > 0.05). However, the mean morphometric values tended to be slightly higher—by 1.72–3.69%—compared to the SNI standard. The Q–Q Plot analysis indicated that morphometric data of female Madura cattle across all grades were normally distributed, with grade 1 showing greater variation than grades 2 and 3.